3D visualisation and dating of an embedded chert artefact from Barrow Island. (June 2016) - Ward, I.; Salvemini, F.; Veth, P.
Abstract: This paper presents 3D visualisations of a non-local chert manuport embedded in a dune-deposited calcrete on Barrow Is., North West Australia. The use of non-destructive high-resolution neutron tomography provides critical visual evidence of any fracture surfaces on the embedded section of the chert, and of likely weathering before the chert manuport finally became cemented within the calcrete. Uranium-series dating of the calcrete and luminescence dating of the overlying dune sands indicates a likely age of ~ 41–14.5 ka for the manuport, corresponding with the antiquity of the archaeology elsewhere on the island. The results highlight the potential of neutron tomography to resolve and document structural and morphological features of embedded archaeological materials without the need for invasive procedures. Highlights: Use of non-invasive methods to provide 3D visualisation of an embedded chert manuport Minimum and maximum age dating of the chert manuport